Al-Ma'tsurat Zikr in Hadith Review: A Case Study of Students at Baitul Quran Al-Ghifari - Yusuf, Muhammad; Farid Adnir (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines the analysis of hadith in the practice of Al-Ma’tsurat dhikr by students of Baitul Quran Al-Ghifari Islamic boarding school, located in Kecamatan Hamparan Perak, Desa Lama. The research aims to evaluate the authenticity and application of hadith used in Al-Ma’tsurat dhikr and its impact on the students’ spiritual, psychological, and social well-being. The research employs a qualitative approach, utilizing methods such as observation, interviews, and documentation. Data analysis involves evaluating the sanad (chain of narrators) and matan (content) of the hadiths to determine their authenticity, followed by examining the implementation and benefits of Al-Ma’tsurat dhikr among the students. The findings indicate that the majority of the dhikr in Al-Ma’tsurat are based on authentic (sahih) and reliable (hasan) hadiths, with a few exceptions of weak (dhaif) hadiths. The regular practice of Al-Ma’tsurat dhikr significantly enhances the students' tranquility, reduces stress, strengthens their faith, and fosters solidarity and togetherness within the community. Additionally, the practice of dhikr helps in the formation of disciplined and spiritually strong characters among the students. This research highlights the importance of ensuring the authenticity of hadiths used in religious practices and the significant benefits of regular dhikr practice in educational settings. The study concludes with recommendations for reinforcing dhikr materials, developing comprehensive dhikr programs, enhancing educational quality, and conducting further research on the broader impacts of dhikr.